Prevalence of Rocahepevirus ratti (rat hepatitis E virus) in humans and rats in China - Xiuji Cui; Jianwen Situ; Ting Tang; Zhiyu Li; Dongzhui Chen; Stanley Siu-Fung Ho; Hiu-Laam Chung; Tsz-Chung Wong; Yonghao Liang; Chaowen Deng; Yongxian Su; Huijun Cai; et al. (JHEP Reports)
Background & Aims: Rocahepevirus ratti (rat hepatitis E virus; rHEV) is a ubiquitous pathogen of rats that has recently emerged as a cause of hepatitis in humans. Although several rHEV cases have been detected worldwide, the extent of human exposure to this hepatitis agent is still poorly defined. We conducted a multicenter surveillance study in China examining rHEV exposures in demographically diverse human populations from a One Health perspective. Methods: In this multicenter cross-sectional study, we used fully validated rHEV IgG enzymatic immunoassays and reverse transcription PCR in 1,199 individuals with (n = 655) or without hepatitis (n = 544) recruited from three centers in China (Hainan, Hong Kong, and Shenzhen). The patient population included both urban and rural populations. Characteristics of infected individuals and phylogenetic links with rat epizootics were described. Results: rHEV IgG seroprevalence was higher in the rural Hainan cohort (15/229, 6.6%) compared with Shenzhen (9/427, 2.1%) and Hong Kong cohorts (2/543, 0.4%) (p <0.0001). This difference persisted on multivariable logistic regression with an adjusted odds ratio of 20.52 (95% CI: 13.86–30.39). rHEV exposure was also associated with increasing age and environmental rodent exposure. We observed rHEV viraemia in two hepatitis patients (2/655; 0.3%) in Hainan and Hong Kong with hepatitis B and renal transplantation, respectively. The latter developed chronic hepatitis E. 19/509 (3.7%) rats captured in Hainan harbored rHEV. Both human rHEV isolates were phylogenetically related to rodent-derived rHEV strains circulating in Hainan and Hong Kong, respectively. Conclusions: Humans are intermittently exposed to rHEV, especially in rural settings with rodent exposure. Overt hepatitis occurs in individuals with liver disease or immunosuppression. Spillover strains are related to epizootics in rodents offering opportunities for targeted disinfestation. Impact and implications: Building on our previous work finding that Rocahepevirus ratti (rHEV) is a novel cause of sporadic viral hepatitis in humans, we studied rHEV exposures in humans from various epidemiological settings. We found intermittent exposure to rat hepatitis E in individuals living in both urban and rural settings with a markedly higher seroprevalence in the latter. Spillover viremic infections in individuals with underlying liver disease or immunosuppression were closely linked to epizootic rHEV strains circulating in rodents. Physicians and diagnostic laboratories should incorporate rHEV testing in algorithms for viral hepatitis while policymakers should consider rHEV surveillance in rodents to guide disinfestation efforts.